Gender Trauma in Africa: Enhancing Women's Links to Resources - Tamale, Sylvia (Journal of African Law, 2004)
The article considers the impact of the public/private divide on the lives of African women. It discusses how the “protection” of the private from legal and other scrutiny helps to conceal the burden of caring for family which is borne almost exclusively by women. Moreover, the devaluation and non-recognition of women's labour in “private” family enterprises is reinforced by the inequitable division and enjoyment of property, not least land. Indeed, often women's access to resources is, like their access to political fora, severely curtailed, thus calling into question the notion that women are full citizens. The paper calls for a transformation of gender relations on the continent. It argues that there needs to be a reconceptualization of African citizenship to embrace women's experiences and that this can only be done by addressing the socio-structural inequalities which hamper women's participation in society.